2016
DOI: 10.1155/2016/3195492
|View full text |Cite
|
Sign up to set email alerts
|

A New Wavelet Threshold Function and Denoising Application

Abstract: In order to improve the effects of denoising, this paper introduces the basic principles of wavelet threshold denoising and traditional structures threshold functions. Meanwhile, it proposes wavelet threshold function and fixed threshold formula which are both improved here. First, this paper studies the problems existing in the traditional wavelet threshold functions and introduces the adjustment factors to construct the new threshold function basis on soft threshold function. Then, it studies the fixed thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 11 publications
(12 reference statements)
0
37
0
Order By: Relevance
“…Thus, it can be concluded that Ψ Ψ is always positive semidefinite. Positive semidefinite property guarantees that MSE(X, ) is convex while invertible of Ψ Ψ makes the optimal solution of a in the form of (10), (12) and (29), (33). It must be full rank to ensure invertible Ψ Ψ, so we can deduce that Ψ must be full row or column rank because of rank(Ψ) = rank(Ψ Ψ).…”
Section: Optimal Solution Guaranteementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be concluded that Ψ Ψ is always positive semidefinite. Positive semidefinite property guarantees that MSE(X, ) is convex while invertible of Ψ Ψ makes the optimal solution of a in the form of (10), (12) and (29), (33). It must be full rank to ensure invertible Ψ Ψ, so we can deduce that Ψ must be full row or column rank because of rank(Ψ) = rank(Ψ Ψ).…”
Section: Optimal Solution Guaranteementioning
confidence: 99%
“…In addition, the more important drawback is that soft and hard threshold functions do not have continuous derivatives. Various improvements had been proposed by exploring new threshold functions [1,[10][11][12][13][14][15][16][17], but the nonnegative garrotelike functions [10][11][12][13][14] are still not differentiable. Zhang [1,15], Nasri and Nezamabadi-pour [16], and Wu et al [17], respectively, proposed a series of threshold functions with adjustable parameters.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Thresholding Function. The basis thresholding functions are soft and hard thresholding functions [18]; the soft thresholding function is as follows:…”
Section: Key Factors Of Wavelet Threshold Denoising Methodmentioning
confidence: 99%
“…In addition, it can be integrated with other smoothing methods to improve the denoising outputs of sensors' measurements [31,32]. The energy of wavelet decompositions is the main parameter for signal denoising [33,34]. The analyzed signal can be decomposed into high and low wavelet energy components according to the oscillatory behavior of the signal components.…”
Section: Introductionmentioning
confidence: 99%